Macroeconomics, sharia, and economic inequality in The Organization of Islamic Cooperation (OIC): An empirical study - Zakwan Asrari; Taosige Wau (Jurnal Ekonomi Syariah Teori dan Terapan, 2023)
ABSTRACT This study aimed to determine the factors that influence the level of income inequality in member countries of the Organization of Islamic Cooperation (OC). The research period used was from 2012 to 2021, using the System Generalized Method of Moment (GMM) analysis tool. The variables used consist of the Gini ratio (proxy of income inequality), economic growth, Foreign Direct Investment (FDI), inflation, the average length of schooling (human capital proxy), and corruption perception index (sharia proxy). The results showed that sharia, human, and inflation variables had a negative effect, while economic growth and FDI had a positive and significant effect on income inequality in OIC countries. These results show that in addition to economic factors and human capital, sharia elements cannot be released in overcoming income inequality in OIC countries. Sharia is a driving factor in a more even distribution of income. Keywords: Income Inequality, Organization of Islamic Cooperation (OIC), System Generalized Method of Moment (GMM), Sharia ABSTRAK Penelitian ini bertujuan untuk mengetahui faktor-faktor yang mempengaruhi tingkat ketimpangan pendapatan di negara anggota Organization of Islamic Cooperation (OIC). Periode penelitian yang digunakan adalah dari tahun 2012 sampai dengan tahun 2021, dengan menggunakan alat analisis System Generalized Method of Moment (GMM). Variabel yang digunakan terdiri dari rasio gini (proksi ketimpangan pendapatan), pertumbuhan ekonomi, Foreign Direct Investment (FDI), inflasi, rata-rata lama sekolah (proksi human capital), dan indeks persepsi korupsi (proksi syariah). Hasil penelitian menunjukkan bahwa variabel syariah, human, dan inflasi berpengaruh negatif, sedangkan pertumbuhan ekonomi dan FDI berpengaruh positif  dan signifikan terhadap ketimpangan pendapatan di negara-negara OIC. Hasil ini menunjukkan bahwa selain faktor ekonomi dan human capital unsur syariah tidak bisa dilepaskan dalam mengatasi ketimpangan pendapatan di negara OIC. Syariah menjadi faktor pendorong dalam distribusi pendapatan yang lebih merata. Kata kunci: Ketimpangan Pendapatan, Organization of Islamic Cooperation (OIC), System Generalized Method of Moment (GMM), Syariah